Fire risk analysis over Portugal in the last decades and contributions of satellite Earth observation to evaluate wildfires - Santos, Filippe (2022)
More intense fire seasons have been favored by climate changes around the world, like Russia, Brazil, the USA, Canada and Portugal. In the last years, Portugal experienced numerous severe fire seasons with catastrophic wildfires that caused enormous impacts. This study aimed to investigate the fire risk evolution in Portugal over the last 40 years and the potential of Sentinel missions to monitor wildfires. First, the Fire Weather Index (FWI) from 1980 to 2020, at 0.25° spatial resolution, provided by the ECMWF ERA5 reanalysis based on meteorological variables, was used. FWI monthly mean values and trends were analyzed for four regions of Southern Portugal (Beja, Evora, Faro and Portalegre). Based on these results, the last five years of daily FWI values for the Faro district were evaluated. The results demonstrate that Faro district presented extreme fire risk values, with a peak on August 2, 2018, the day before the Monchique wildfire, which occurred between August 3 and 9 and was the most calamitous wildfire in Portugal during 2018, with almost 27000 ha burned. Lastly, Sentinel-2 and Sentinel-3 imageries were useful to evaluate the fire evolution and fire severity for this episode.